Currency Factors - Aloosh, Arash; Bekaert, Geert (Management Science, 2022)
We examine the ability of existing and new factor models to explain the comovements of G10 currency changes, measured using “currency baskets.” A clustering technique reveals a clear two-block structure in currency comovements, with the first block containing mostly the dollar currencies and the other the European currencies. A factor model incorporating this “clustering” factor and two additional factors, a commodity currency factor and a “world” factor based on trading volumes, fits currency basket correlations much better than extant factors, such as value and carry, do. In particular, it explains on average about 60% of currency variation and generates a root mean squared error relative to sample correlations of only 0.11. The model also fits comovements in emerging market currencies well. Economically, the correlations between currency baskets underlying the factor structure are inversely related to the physical distances between countries. This paper was accepted by Kay Giesecke, finance.